The Handbook of the Neuropsychology of Language 2012
DOI: 10.1002/9781118432501.ch15
|View full text |Cite
|
Sign up to set email alerts
|

What Role does the Cerebellum Play in Language Processing?

Abstract: Beginning with Rolando and Flourens' early nineteenth-century documentation of the role of cerebellar lesions in disturbances of gait, posture, and voluntary coordi nation of movement, the cerebellum has been considered a primary player in motor behavior (Schmahmann, 1997). In 1922, Holmes was the first to document that focal cerebellar lesions produce speech motor de ficits, suggesting a role for the cerebellum in speech production (Holmes, 1922). However, only recently has inter est arisen in exploring the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…The left perisylvian cortex, including canonical Broca's and Wernicke's areas, is known to support gross language processes in healthy adults (Binder et al, ; Friederici, ; Gabrieli, Poldrack, & Desmond, ; Hirata et al, ; Kadis et al, ; Lohmann et al, ; Pei et al, ; Price, ; Purves et al, ; Toga and Thompson, ; Turken and Dronkers, ). However, participation of right perisylvian cortex and subcortical and cerebellar regions in language have also been documented (Berl et al, ; Booth, Wood, Lu, Houk, & Bitan, ; Desmond, Gabrieli, & Glover, ; Ferstl, Neumann, Bogler, & Von Cramon, ; Frings et al, ; Gabrieli et al, ; Houk et al, ; Kellett, Kellett, Stevenson, & Gernsbacher, ; Middleton and Strick, ; Muller and Meyer, ; Murdoch, ; Schmahmann, ; Stoodley, Valera, & Schmahmann, ; Stoodley and Schmahmann, ; Verly et al, ). In particular, seminal anatomical and behavioral studies have shown nonmotor contributions of the (right) cerebellum in a range of cognitive processes, including language (Leiner, Leiner, & Dow, ; Petersen, Fox, Snyder, & Raichle, ; Raichle et al, ; Schmahmann, ; see Price, , for review).…”
Section: Introductionmentioning
confidence: 99%
“…The left perisylvian cortex, including canonical Broca's and Wernicke's areas, is known to support gross language processes in healthy adults (Binder et al, ; Friederici, ; Gabrieli, Poldrack, & Desmond, ; Hirata et al, ; Kadis et al, ; Lohmann et al, ; Pei et al, ; Price, ; Purves et al, ; Toga and Thompson, ; Turken and Dronkers, ). However, participation of right perisylvian cortex and subcortical and cerebellar regions in language have also been documented (Berl et al, ; Booth, Wood, Lu, Houk, & Bitan, ; Desmond, Gabrieli, & Glover, ; Ferstl, Neumann, Bogler, & Von Cramon, ; Frings et al, ; Gabrieli et al, ; Houk et al, ; Kellett, Kellett, Stevenson, & Gernsbacher, ; Middleton and Strick, ; Muller and Meyer, ; Murdoch, ; Schmahmann, ; Stoodley, Valera, & Schmahmann, ; Stoodley and Schmahmann, ; Verly et al, ). In particular, seminal anatomical and behavioral studies have shown nonmotor contributions of the (right) cerebellum in a range of cognitive processes, including language (Leiner, Leiner, & Dow, ; Petersen, Fox, Snyder, & Raichle, ; Raichle et al, ; Schmahmann, ; see Price, , for review).…”
Section: Introductionmentioning
confidence: 99%
“…The cognitive functions of the cerebellum in language processing have attracted much attention over the past few decades. Systematic reviews have been updating related findings [ 104 , 105 , 106 , 107 ]. Studies on language processing have found activity in the cerebellum across various linguistic components: phonological [ 108 , 109 , 110 ], lexico-sematic [ 111 , 112 ], semantic [ 113 , 114 ], syntactic [ 115 , 116 ], and discourse [ 117 ].…”
Section: Discussionmentioning
confidence: 99%